Warriors - Hastings, Max (Harper Perennial, 2006)
An exhilarating and uplifting account of the lives of sixteen 'warriors' from the last three centuries, hand-picked for their bravery or extraordinary military experience by the eminent military historian, author and ex-editor of the Daily Telegraph, Sir Max Hastings.